Toxoplasma gondii-specific IgG avidity testing in pregnant women. (September 2020) - Garnaud, C.; Fricker-Hidalgo, H.; Evengård, B.; Álvarez-Martínez, M.J.; Petersen, E.; Kortbeek, L.M.; Robert-Gangneux, F.; Villena, I.; Costache, C.; Paul, M.; Meroni, V.; Guy, E.; et al.
Abstract: Background: The parasite Toxoplasma gondii can cause congenital toxoplasmosis following primary infection in a pregnant woman. It is therefore important to distinguish between recent and past infection when both T. gondii -specific IgM and IgG are detected in a single serum in pregnant women. Toxoplasma gondii -specific IgG avidity testing is an essential tool to help to date the infection. However, interpretation of its results can be complex. Objectives: To review the benefits and limitations of T. gondii -specific avidity testing in pregnant women, to help practitioners to interpret the results and adapt the patient management. Sources: PubMed search with the keywords avidity, toxoplasmosis and Toxoplasma gondii for articles published from 1989 to 2019. Content: Toxoplasma gondii -specific IgG avidity testing remains a key tool for dating a T. gondii infection in immunocompetent pregnant women. Several commercial assays are available and display comparable performances. A high avidity result obtained on a first-trimester serum sample is indicative of a past infection, which occurred before pregnancy. To date, a low avidity result must still be considered as non-informative to date the infection, although some authors suggest that very low avidity results are highly suggestive of recent infections depending on the assay. Interpretation of low or grey zone avidity results on a first-trimester serum sample, as well as any avidity result on a second-trimester or third-trimester serum sample, is more complex and requires recourse to expert toxoplasmosis laboratories. Implications: Although used for about 30 years, T. gondii -specific avidity testing has scarcely evolved. The same difficulties in interpretation have persisted over the years. Some authors have proposed additional thresholds to exclude an infection of <9 months, or in contrast to confirm a recent infection. Such thresholds would be of great interest to adapt management of pregnant women and avoid unnecessary treatment; however, they need confirmation and further studies.